Imaging of Cenozoic climatic events and bottom water activities at the northeastern flank of Walvis Ridge: A correlation of seismic data with borehole data measurements - Bartels, Thomas (Univ. Bremen, 2008)
Seismic, marine, walvis ridge, bottom currents, climatic events. - The history of sedimentation and current activities at the northeastern flank of Walvis Ridge is investigated by a correlation of multichannel seismic data collected during R/V Meteor Cruise M49/1 in early 2001 with borehole measurements of Ocean Drilling Project (ODP) Leg 208. During Meteor Cruise M 49/1 multi-frequency seismic data were collected using two different seismic sources, in a quasi simultaneous mode in order to get best possible penetration and resolution of the sub-surface structures. Walvis Ridge divides the southeastern Atlantic Ocean into two basins, the Angola Basin to the north and the Cape Basin to the south. It is well known as an impassable barrier for bottom waters which separates Antarctic Bottom Waters (AABW) widely distributed in the Cape Basin from North Atlantic Depth Waters (NADW) in the Angola Basin. The sediments of the northeastern flank of Walvis Ridge are characterized by mostly undisturbed sequences of Cenozoic sediments, with varying thickness of ~150 m at the edge of the Angola Basin and ~450 m at the axis of the ridge. A correlation of seismic data with borehole data was accomplished by calculating synthetic seismograms using GRA density measurements of the cores and an averaged velocity model. This 'simple' event modeling allows to assign ages to the seismic reflectors and to identify key horizons/boundaries like the E/O and the K/T boundaries as well as the ELMO event and deposits of the PETM, representing Cenozoic climatic events. The seismic pattern of these target horizons shows similar properties at the different sites indicating their regional distribution. A special static correction in addition to standard seismic processing steps resulted in high quality high resolution deep sea Watergun images. A comparison between the seismic images and the magnetic core . thesis